Sedulur Papat as the Source of the Creation of the Dance Work "DEG" - Kinasih, Nadiya; Prihantoro, Wahyu; Wahyudianto; Windrowati, Trinil; Muzaqqi, Ahmad (GETER : Jurnal Seni Drama, Tari dan Musik, 2024)
This dance work explores the concept of deg, which metaphorically represents the human heartbeat as a response to surprising stimuli. The focus lies on external stimuli that evoke profound reactions, reflecting a broader interpretation of Javanese philosophy. The creation delves into the concept of "Let me go," which is transformed into the four human elements: supiyah, aluuwamah, mutmainah, and amarah. These elements embody human desires and are rooted in the philosophy of seddulur papat lima pancer. The choreography employs a creative method inspired by the creator's empirical experiences, blending principles of East Javanese, Malangan, and Surabayan dance movements. The work expresses the philosophical and existential values of human nature through the selection of movements, floor patterns, and the integration of artistic elements such as music, lighting, and props. The atmosphere is built intentionally to align with the underlying themes and to highlight the philosophical essence of the human experience. This creation aims to contribute to the evolution of dance performances by interpreting and modernizing traditional philosophies. It offers a fresh perspective on regional dance idioms, employing innovative movement choices and floor designs to inspire new dance compositions. By bridging traditional elements with contemporary interpretation, the work seeks to enrich the discourse on dance as a medium for reflecting human existence and cultural identity.